Q. 15 A4.3( 6 Votes )

# Prove the following identities :(1 – cosθ)(1+ cosθ)(1+ cot2 θ) = 1

Taking LHS = (1 – cosθ)(1+ cosθ)(1+ cot2 θ)

Using identity , (a + b) (a – b) = (a2 – b2) in first two terms , we get

= (1)2 – (cosθ)2 (cosec2 θ) [ cot2 θ +1= cosec2 θ]

= (1 – cos2 θ) (cosec2 θ)

= (sin2 θ) (cosec2 θ) [ cos2 θ + sin2 θ = 1]

=1

= RHS

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Trigonometric Identities33 mins
Trigonometric Identities33 mins
NCERT | Trigonometric Identities52 mins
Quiz | Task on Trigonometric Ratios46 mins
Algebraic Identities48 mins
Quiz | Practice Important Questions on Trigonometrical Identities46 mins
Quiz on Trigonometric Ratios31 mins
T- Ratios of Specified Angles58 mins
Trick to learn all Trigonometric Formulae28 mins
Testing the T- Ratios of Specified Angles57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses